1999
DOI: 10.1002/(sici)1097-4628(19991114)74:7<1607::aid-app1>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

On melt-crystallization of polytetrafluoroethylene and of random fluorinated copolymers of tetrafluoroethylene

Abstract: Through differential scanning calorimetry, isothermal crystallization from the melt of polytetrafluoroethylene (PTFE) has been investigated. PTFE was regarded as one of the polymers for which crystallization is so rapid that the samples crystallize during the cooling from the melt to the selected crystallization temperature. By contrast, we now report that a stochastic behavior is observed for isothermal melt-crystallization of PTFE. In fact, on cooling very quickly the samples from the molten state to the sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…After annealing at ambient pressure in N 2 either at 290 or 330 8C, DH f was not distinguishable from as received samples within experimental error. Evidently, thermal annealing is insufficient to increase the degree of crystallinity perhaps due to extremely rapid crystallization [28].…”
Section: Crystallinity Of Ptfe Annealed Under Various Conditionsmentioning
confidence: 99%
“…After annealing at ambient pressure in N 2 either at 290 or 330 8C, DH f was not distinguishable from as received samples within experimental error. Evidently, thermal annealing is insufficient to increase the degree of crystallinity perhaps due to extremely rapid crystallization [28].…”
Section: Crystallinity Of Ptfe Annealed Under Various Conditionsmentioning
confidence: 99%
“…In fact, it was reported that for PTFE, crystallization is so rapid that the sample crystallizes during the cooling from the melt to the selected crystallization temperature 25. Nevertheless, in an article in press, 26 we have shown that it is possible, by carefully controlling the experimental conditions, to perform isothermal melt‐crystallization experiments even for this polymer. Moreover, in the past, the equilibrium melting temperature of PTFE was determined from data of melting temperature as a function of the lamellar thickness, 27 a method strictly related to that used by Hoffmann and Weeks 22.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have reported that superheating is higher (Tm ≈ Tm0 + 10 ∘ C, where the equilibrium melting temperature Tm0 has been reported in the range of 332-336 ∘ C) [15][16][17][18]. Pucciariello et al applied MDSC in the quasi-isothermal mode to investigate melting and crystallization of PTFE [19,20]. They confirmed the strong differences in the melting temperature of meltcrystallized and as-polymerized PTFE.…”
Section: Resultsmentioning
confidence: 99%